Pengaruh Gear Ratio Transmisi dan Grade Jalan Terhadap Fuel Consumption Truck Batubara dengan Pendekatan Regresi Linier Berganda - Nuryono, Arif (Journal of Industrial and Engineering System, 2020)
Transmission Gear Ratio usually affects torque and speed. The effect on fuel consumption for coal trucks with a capacity of 20 tons needs technical analysis and experiment to obtain actual data. In the experiment process using a standard transmission issued by the factory that is with 8 forward speed and 1 reverse speed. Experiment is done by comparing the calculation of fuel consumption with the use of transmission. Tests carried out using 2 dump trucks, 6 times sampling, 8-Speed, 30 km distance, with variations in the grade 8 segments and loads. From the results of testing and calculation of fuel consumption with parameter 8 variations in road grade and loaded, different fuel usage is obtained for each road segment and in load or empty conditions. When high grade fuel consumption also increases, when loaded conditions fuel consumption increases. Road grade and loaded conditions affect the use of fuel consumption. The use of transmission speed or gear ratio also affects fuel consumption.